Psychoeducation and Resilience Building for Students from Broken Homes: an Intervention Study at SMKN 1 Girisubo - Suratmi Lestari; Nurhasanah Putri; Hanan Akilah; Yusriyyah Al Mufiidah; Nurul Hidayah (Riviera Publishing, 2026)
The phenomenon of broken home families is a significant risk factor for adolescent mental health, particularly in terms of emotion regulation and resilience. This study aimed to test the effectiveness of a psychoeducation and resilience-building program for students from broken home families at SMKN 1 Girisubo. The study used a pre-experimental one-group pretest–posttest design involving 37 students. The intervention was carried out through psychoeducation, emotion regulation training, and the strengthening of coping strategies. Data were analyzed using descriptive statistics and a paired-samples t-test. The results showed no significant differences in the variables of broken home status (p = 0.715) and resilience (p = 0.947). However, descriptively, there was an increase in students’ psychological understanding. These findings indicate that short-term interventions were not yet effective in increasing resilience; therefore, a more intensive and sustainable approach is needed.